Pure Endovascular versus Hybrid Approach for Management of Iliofemoral Arterial Disease: A Randomized Controlled Trial - Shaker, Ahmed A.; Shehata, Ahmed H.; Alhindawy, Khaled M.; El Daly, Walid (International Journal of Angiology, 2022)
Common femoral artery (CFA) atherosclerotic lesions currently remain one of the last limitations for adoption of endovascular repair as the first-line treatment, easy surgical accessibility, and, last but not least, favorable long-term outcomes, still making CFA disease treatment part of the surgical domain. In the last 5 years, improvement of the endovascular equipment and technical skills of the operators have led to an increase in percutaneous CFA procedures.A single-center randomized prospective study of 36 symptomatic (Rutherford 2–4) CFA stenotic or occlusive lesions were included, and patients were randomized over two groups based on the management approach SUPERA versus hybrid technique.Patients had a mean age 60.8 ± 8.2 years. Thirty-two (88.9%) patients reported improvement of the clinical symptoms, 28 (87.5%) patients had intact pulse postoperatively, and 28 (87.5%) had patent vessels. Follow-up showed that none developed reocclusion or restenosis during the period of follow-up. Comparison of difference in peak systolic velocity ratio (PSVR) among study groups showed that the hybrid technique had more reduction of PSVR postintervention compared to the SUPERA group with a p-value of < 0.0001.Safety and feasibility of endovascular approach with the SUPERA stent to the CFA (no stent zone) has low incidence of postoperative morbidity and mortality in well experienced surgical hands.
Keywords: SUPERA; common femoral artery; endarterectomy; hybrid